2005
DOI: 10.1007/s00213-005-0170-9
|View full text |Cite
|
Sign up to set email alerts
|

ACP-103, a 5-HT2A/2C inverse agonist, potentiates haloperidol-induced dopamine release in rat medial prefrontal cortex and nucleus accumbens

Abstract: These data suggest that the relative extent of 5-HT(2A) and 5-HT(2C) antagonism, as well as the extent of D(2) receptor blockade, has a critical influence on DA release in the mPFC and NAC and may be a determining factor in the action of this class of atypical APDs on these two potentially clinically relevant parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 34 publications
3
39
0
Order By: Relevance
“…On the other hand, haloperidol increased DA levels in the frontal cortex of Nur77 +/+ mice as previously reported (Li et al 2005), but this effect is blunted in Nur77 −/− mice. Since COMT is mandatory for DA clearance in the frontal cortex (Bilder et al 2004), one might expect that reduced COMT levels would have instead exacerbated haloperidol effects on DA levels in Nur77 −/− mice.…”
Section: Discussionsupporting
confidence: 88%
“…On the other hand, haloperidol increased DA levels in the frontal cortex of Nur77 +/+ mice as previously reported (Li et al 2005), but this effect is blunted in Nur77 −/− mice. Since COMT is mandatory for DA clearance in the frontal cortex (Bilder et al 2004), one might expect that reduced COMT levels would have instead exacerbated haloperidol effects on DA levels in Nur77 −/− mice.…”
Section: Discussionsupporting
confidence: 88%
“…Recent data suggests that atypical antipsychotic medications change lipid metabolism (Ferno et al, 2005), an effect that may also be related to the weight gain associated with many atypical antipsychotics (Bartzokis, 2002). Other mechanisms are consistent with neurochemicallybased models that suggest increased prefrontal cortex dopaminergic neurotransmission underlies some of the beneficial effects of atypical antipsychotics (Barch and Carter, 2005;Eltayb et al, 2005;Li et al, 2005). Consistent with the possibility that this effect could be mitigated by oligodendrocytes, in vitro models have suggested that dopamine stimulation may be protective of oligodendrocytes (Belachew et al, 1999;Rosin et al, 2005) and/or promote the genesis of new cells (Van Kampen et al, 2004).…”
Section: Discussionmentioning
confidence: 65%
“…Shilliam and Dawson (2005) demonstrated that this increase was confined to the shell of the NAc and did not occur in the NAc core. We have previously shown that 5-HT 2C -receptor antagonism, in combination with D 2 -receptor antagonism, may contribute to the ability of these agents to enhance DA release in the NAc (Bonaccorso et al, 2002;Li et al, 2005). The potent 5-HT 2C antagonist, SB242084, significantly potentiated low-dose haloperidolinduced increase in DA release in the NAc .…”
Section: Da Effluxmentioning
confidence: 95%
“…ASE, in this study, at doses less than 0.5 mg/kg, also showed preferential increase in cortical and HIP DA efflux compared with in the NAc. This action is due, in part, to blockade of 5-HT 2A receptors in the cerebral cortex and relatively weaker or negligible occupation of D 2 and D 1 receptors (Matsubara et al, 1993), since it can be mimicked by the combination of potent 5-HT 2A antagonism and weak blockade of D 2 receptors (Liegeois et al, 2002;Bonaccorso et al, 2002;Li et al, 2005). As reported by Schotte et al (1996), these agents, including clozapine, risperidone, 9-hydroxyrisperidone (paliperidone), olanzapine, pipamperone, quetiapine, sertindole, ziprasidone, and zotepine, also have higher occupancy in the rat cortex and striatum of 5-HT 2A than D 2 receptors, respectively, at all but the highest doses studied.…”
Section: Da Effluxmentioning
confidence: 99%
See 1 more Smart Citation